1975
DOI: 10.1073/pnas.72.7.2829
|View full text |Cite
|
Sign up to set email alerts
|

Slow growth rate of a deep-sea clam determined by 228Ra chronology.

Abstract: The age of a deep-sea clam, Tindaria caifisti-formis, from 3800 m depth has been determined by MRa (6.7 year half-life) chronology of separated size fractions of a captured population. A length of 8.4 mm is attained in about 100 years. Shells of this size fraction show about 100 regularly spaced bands, indicating that the growth feature may be an annual one.There are several reports indicating that the rate of metabolism on the deep ocean floor is extremely slow-generally one to two orders of magnitude slow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
31
0

Year Published

1982
1982
2014
2014

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 100 publications
(35 citation statements)
references
References 9 publications
4
31
0
Order By: Relevance
“…The longest living animals belong to the Bivalvia (Bureau et al, 2002;Peck and Bullough, 1993;Turekian et al, 1975;Ziuganov et al, 2000;Wanamaker et al, 2008;Butler et al, 2013), a main class in the phylum Mollusca. Long-lived animals have been defined as non-senescing species (Finch and Austad, 2001) because they do not show any observable age-related decline in physiological capacity or disease resistance.…”
Section: Introductionmentioning
confidence: 99%
“…The longest living animals belong to the Bivalvia (Bureau et al, 2002;Peck and Bullough, 1993;Turekian et al, 1975;Ziuganov et al, 2000;Wanamaker et al, 2008;Butler et al, 2013), a main class in the phylum Mollusca. Long-lived animals have been defined as non-senescing species (Finch and Austad, 2001) because they do not show any observable age-related decline in physiological capacity or disease resistance.…”
Section: Introductionmentioning
confidence: 99%
“…An alternative approach involves the use of chronometers incorporated into the shell during growth. Naturally occurring radionuclides of the uranium and thorium decay series have been used to determine the growth rates of a variety of marine organisms [6][7][8][9][10][11][12][13][14][15][16]. In particular, the radionuclides 228Ra (half-life=5.75 y) and 21°Pb (half-life=22 y) present in sea water are incorporated into the shells of marine organisms where they undergo radioactive decay to 228Th (half-life = 1.9 y) and 2a°Po (half-fife= 138 days), respectively.…”
Section: Introductionmentioning
confidence: 99%
“…Further work on profiles in the Atlantic Ocean, as part of the GEOSECS campaign at Lamont under Wally Broecker, affirmed the high concentration of 228 Ra in the ocean bottom, and other studies indicated high values in deep-sea sediment pore waters (Trier et al 1972). So, brashly, we determined the growth rate of Tindaria using the bands and the 228 Ra-based age (Turekian et al 1975). The largest clam (8 mm) was about 100 years old and, on the basis of comparison with shallow water clams, probably reached puberty at about 40 years.…”
Section: Sea Shellsmentioning
confidence: 99%